Potentiel de maturation du cépage Touriga Nacional dans différents itinéraires technologiques et régions (Dão, Bairrada et Vinhos Verdes) - Castro, Rogério (2013)
Foreseeing climatic changes, the abnormally hot and dry year of 2005 can be revealer of some varieties behavior in different climatic conditions. In three experiments, done in private companies, (Dão Sul, Caves Messias and Quinta de Lourosa), the behavior of ‘Touriga Nacional’ vine variety, with different technological itineraries, was studied. In Dão, it was evaluated the influence of shoot density (23, 17 and 11 for linear meter of canopy) and qualitative cluster thinning at veraison. In Bairrada, the traditional vine trellising has been compared with the Lys system. In both conduction systems has been evaluated the influence of qualitative cluster thinning at veraison. In Vinhos Verdes, in the system LYS 2/3, has been studied the effect of shoot density (29 and 20 for linear meter of canopy) and leaf removal associated to qualitative cluster thinning at veraison. In these three regions, two of them that are not traditional places for this variety, the ‘Touriga Nacional’ reached high levels of yield and quality, in adjusted technological itineraries. Cluster thinning reduced yield in all cases, as it was expectable, with gains of PAC only in Bairrada. In a general way, different levels of canopy management (leaf removal and shoot suppression) didn’t play an important role. In Dão, the greatest shoot density originated a higher yield, without quality decrease. In these three regions, two of which not traditional of this chaste one, the Touriga Nacional disclosed high levels of In a global way, the ‘Touriga Nacional’ vine variety demonstrated high potentials of yield and maturation, in all regions. But in situations of high hydric stress, as verified in Bairrada, the reduction of production lead to significant improvements of quality.